2021
DOI: 10.1126/sciadv.abg4934
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic resistance induces cell phenotypic transition in confinement

Abstract: Cells penetrating into confinement undergo mesenchymal-to-amoeboid transition. The topographical features of the microenvironment expose cells to different hydraulic resistance levels. How cells respond to hydraulic resistance is unknown. We show that the cell phenotype shifts from amoeboid to mesenchymal upon increasing resistance. By combining automated morphological tracking and wavelet analysis along with fluorescence recovery after photobleaching (FRAP), we found an oscillatory phenotypic transition that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 38 publications
1
19
1
Order By: Relevance
“…These authors reported that TRPM7 knockdown conferred a "contractile" phenotype, suppressed migration velocity and wound closure, and metastasis (45). These findings are in distinct contrast to (i) the "slender" shape observed in prior studies (8,40) and in this work, (ii) our previous data showing that TRPM7 promotes actomyosin contractility (9), and (iii) the slower track velocity and displacement at the front of in vivo tumors of HT-1080 cells overexpressing TRPM7. It is also noteworthy that Kaplan-Meier analysis of human patients shows that patients with osteosarcoma, breast, gastric, and liver cancer expressing high levels of TRPM7 had improved survival (fig.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…These authors reported that TRPM7 knockdown conferred a "contractile" phenotype, suppressed migration velocity and wound closure, and metastasis (45). These findings are in distinct contrast to (i) the "slender" shape observed in prior studies (8,40) and in this work, (ii) our previous data showing that TRPM7 promotes actomyosin contractility (9), and (iii) the slower track velocity and displacement at the front of in vivo tumors of HT-1080 cells overexpressing TRPM7. It is also noteworthy that Kaplan-Meier analysis of human patients shows that patients with osteosarcoma, breast, gastric, and liver cancer expressing high levels of TRPM7 had improved survival (fig.…”
Section: Discussioncontrasting
confidence: 68%
“…In line with these observations, chelation of extracellular calcium with BAPTA or inhibition of ROCK activity or myosin-II function blocked the shear-induced directional change of fibroblasts, thereby promoting their intravasation in the presence of shear flow. Although fibroblasts typically exhibit a mesenchymal phenotype, their exposure to fluid shear triggers RhoA activation, which supports a bleb-based phenotype (17,18,40). Along these lines, half of the fibroblasts, which reversed migration direction to avert exposure to fluid flow, displayed a blebbing phenotype.…”
Section: Discussionmentioning
confidence: 91%
“…This difference suggests that cells will reorganize their cytoskeleton structure upon external mechanical input. Experimentally, it has indeed been observed that the actin network can further polarize towards the front of the cell when cells experience high external hydrostatic pressure ( Zhao et al, 2019 ; Zhao et al, 2021 ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Increased cation entry can affect cellular function directly or by enhancing intracellular signaling cascades which lead to the downstream release of calcium ( Pedersen and Nilius, 2007 ; Petho et al, 2019 ). Importantly, TRP channels also regulate the proliferation, differentiation, migration, invasion and chemoresistance of cancer cells by sensing osmotic perturbations, shear forces and hydrostatic pressure ( Clapham, 2003 ; Liedtke et al, 2003 ; Gomis et al, 2008 ; Mendoza et al, 2010 ; Shen et al, 2015 ; Zhao et al, 2019 ; Yankaskas et al, 2021 ; Zhao et al, 2021 ) ( Table 1 ). Several members of the TRP superfamily also participate in actin remodeling and focal adhesion dynamics in response to mechanical stimuli ( Kobayashi and Sokabe, 2010 ; Shen et al, 2015 ; Zhao et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…CRISPR/Cas9 knockout of TRPM7 blinds cells to hydraulic resistance and causes them to choose migratory paths based on cross-sectional area ( Zhao et al, 2019 ). TRPM7 not only influences the directional navigation of cancer cells but also provides cells with plasticity to counter elevated hydraulic resistances ( Zhao et al, 2021 ). Elevated hydraulic resistance induces a shift in cell migration phenotype from amoeboid to mesenchymal ( Zhao et al, 2021 ), which relies on the formation of actin-rich lamellipodia and integrin-based cell-matrix adhesions rather than membrane blebs ( Friedl and Wolf, 2010 ; Pankova et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%